2011
DOI: 10.2320/matertrans.l-mz201126
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation of the Microstructure and Mechanical Behaviour of 2024 Aluminium Alloy Friction Spot Welds

Abstract: Friction Spot Welding (FSpW) is a new solid-state joining process able to produce similar and dissimilar overlap connections in different classes of materials. Advantages of this new technique are: short production cycles, high performance joints, absence of filler materials and good surface finishing supported by material refilling in the spot area. Although few authors have addressed the microstructural and mechanical behavior of friction spot welds of Aluminum alloys, there is still a lack of a systematic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 11 publications
3
44
0
7
Order By: Relevance
“…A Figura 9 apresenta as especificações mínimas de resistência para as tecnologias de união em questão. Os dados da curva do processo RSW referemse às ligas de Al cujos valores da tensão limite de resistência à tração são superiores a 386 MPa, que é o caso da liga 2024-T3, com um valor de aproximadamente 425 MPa [35]. Quanto à curva de rebitagem, os dados referem-se a rebites do tipo sólido do mesmo material.…”
Section: Soldagem Por Ponto No Estado Sólido De Ligas Levesunclassified
See 1 more Smart Citation
“…A Figura 9 apresenta as especificações mínimas de resistência para as tecnologias de união em questão. Os dados da curva do processo RSW referemse às ligas de Al cujos valores da tensão limite de resistência à tração são superiores a 386 MPa, que é o caso da liga 2024-T3, com um valor de aproximadamente 425 MPa [35]. Quanto à curva de rebitagem, os dados referem-se a rebites do tipo sólido do mesmo material.…”
Section: Soldagem Por Ponto No Estado Sólido De Ligas Levesunclassified
“…Para efeito de comparação, a carga de cisalhamento da liga de Al 2024-T3 da Figura 8 equivale a aproximadamente 10,1 kN em chapas de 2 mm de espessura [35]. Considerando uma junta sobreposta obtida por RSW em chapas de mesma dimensão, a resistência ao cisalhamento estabelecida é de 5 kN.…”
Section: Soldagem Por Ponto No Estado Sólido De Ligas Levesunclassified
“…The SZ is characterized by fine grain structure due to dynamic recrystallization [4,9,16,21]. This region underwent severe plastic deformation due to the sleeve and pin movement and was exposed to high temperature, as illustrated in Figure 6c.…”
Section: Microstructure Evaluationmentioning
confidence: 99%
“…This joining process does not increase the weight of the structure because no additional fastener or rivet is used. Compared to conventional fusion welding processes, refill FSSW consumes less energy and produces joints with a good surface finish [4,5]. Some published works [5][6][7][8][9][10][11][12][13][14][15] have reported that refill FSSW has been successfully used to weld relatively thin materials, up to 2-mm-thick, in similar and dissimilar joint combinations with good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation